Effect of VR simulations on MPA level & breath control of voice major students - Haris, Thio Felicia Yasinta; Purbojo, Rijanto (Universitas Negeri Yogyakarta, 2024)
A form of art that is created through a performance by one or an ensemble of performers, shown in front of an audience is called the performing arts. Despite having its appeal, performing in front of many people can lead to